PENGARUH LAMA FERMENTASI TERHADAP KADAR ALKOHOL TAPE SINGKONG (Manihot utilissima Pohl). - Hasanah, Hafidatul; Jannah, Akyunul; Fasya, Ahmad Ghanaim (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2012)
Tape is one of the products of fermentation. Of the agreement MUI, foods and beverages containing alcohol should not exceed 1%, so the food / drinks that contain high levels of alcohol exceeding 1% are included in the category of haram for consumption. This study aimed to determine the effect of fermentation time on ethanol content of cassava (Monihotutilissima Pohl) tapai. The method that is used to separate the two or more component of volatile and non volatile from tapai is called distillation while to analyze an ethanol level used gas chromatography (GC) method. To examine the data which differentiate the base concentration of alcohol (%) in cassava tapai since fermentationprocess which were analyzed by variants analysis (ANOVA). In the next experiment, if there was different significant result, then continued by the test of BNT which the level for about 1%.The samples of cassava (Monihot utilissima Pohl) tapai fermented for about 24, 48, 72, 96 and 120 hours. Those tapai were mashed and added the aquades. The mixed materials were distillated, then entered into the bottle and considered as gram unit. The considered distillations were being analyzed used gas chromatography (GC) method.The result of the research showed that there is the influence of long fermentation to ethanol level’s of cassava (Manihot utilissima Phol) tapai. The level of cassava ethanol was 0.844%, 2.182%, 4.904%, 6.334% and 11.811%. The long fermentation was for about 120 hours and it was an indeed influence (p 0,01) to the level of cassava’s ethanol among the period of long fermentation.